Islet cell autoantigens in insulin-dependent diabetes. - Atkinson, M A (1993)
A burgeoning number of antigenic targets of the islet cell autoimmunity in IDD have been identified, and more can be anticipated through improved methods for their identification. The challenge for those investigating the pathogenesis of IDD will be to assign the relative importance of these antigens to the development of the disease, and to resolve whether there is a dominant primary immunologic event that is followed by a series of secondary immunizations to a variety of normally sequestered islet cell antigens in the sequence of pathogenic events that culminate in IDD. One interesting observation that may have potential pathogenic implications is the observation that of all islet cell autoantigens described, only two (i.e., 64 kD/GAD, 38 kD) are reactive in their native configurations, implying that recognition of conformational epitopes is most important. This property argues for primary immunizing agents rather than secondary ones after release of denatured antigens and antigenic recognition through their epitopes. Given the complex and multiple physiological functions of islet cells and the continuous variation in their activity, it is reasonable to speculate that the speed of the progression to IDD could vary between individuals with respect to their insulin needs and the relative activities of their islets. Activated islets may express autoantigens that have only limited expression in quiescent islets. The often times striking variation in the severity of insulitis seen in different islets of a single pancreas may be explained by the level of activity of individual islets. Furthermore, disparity in HLA-DR/DQ associations with disease may involve differences in the immunological recognition of autoantigens. Whereas there is still much to learn, it is clear that disease predictability and disease intervention studies have been enhanced through the identification of the islet cell autoantigens in IDD.